2017
DOI: 10.1016/j.postharvbio.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Astringency assessment of persimmon by hyperspectral imaging

Abstract: One of the current challenges of persimmon postharvest research is the development of non-destructive methods that allow determination of the internal properties of the fruit, such as maturity, flesh firmness and astringency. This study evaluates the usefulness of hyperspectral imaging in the 460-1020 nm range as a non-destructive tool to achieve these aims in Persimmon cv. 'Rojo Brillante' which is an astringent cultivar. Fruit were harvested at three different stages of commercial maturity and exposed to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Regarding persimmon firmness, 3 (580, 680, and 1050 nm) and 5 (570, 590, 680, 710, and 990 nm) feature wavelengths were, respectively, chosen by PCA and SPA. These 2 groups of wavelengths were then used as independent variables in PLSR models to predict persimmon firmness, yielding the same accuracy ( R 2 P = 0.80) (Munera and others , ). NIR multispectral imaging (900 to 1700 nm) has also been extensively used to measure the physical attributes of plant foods.…”
Section: Determination Of Quality Parameters Of Plant Foodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding persimmon firmness, 3 (580, 680, and 1050 nm) and 5 (570, 590, 680, 710, and 990 nm) feature wavelengths were, respectively, chosen by PCA and SPA. These 2 groups of wavelengths were then used as independent variables in PLSR models to predict persimmon firmness, yielding the same accuracy ( R 2 P = 0.80) (Munera and others , ). NIR multispectral imaging (900 to 1700 nm) has also been extensively used to measure the physical attributes of plant foods.…”
Section: Determination Of Quality Parameters Of Plant Foodsmentioning
confidence: 98%
“…As shown in Figure , it is observed that the soluble dietary fiber content in celery decreases with an extension of storage time, while the insoluble dietary fiber content keeps increasing (Yan and others ). For visualizations of caffeine content in coffee bean, tannins in persimmon, and starch content (SC) in potato and sweet potato tubers, PLSR models in combination with wavelength selection methods (such as RF, SPA, and FMCIA) performed the best (Zhang and others ; Munera and others ; Su and Sun ). In a recent study by Su and Sun (), the simplest FMCIA‐MLR and FMCIA‐PLSR models that were developed with only 6 feature variables resulted in very high R 2 P of 0.962 and 0.963 for detecting tuber dry matter content (DMC) and SC, respectively.…”
Section: Determination Of Quality Parameters Of Plant Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques based on the spectrum analysis, like hyperspectral imaging, have been widely used for the qualitative and quantitative determination of different properties in fruit (Lorente et al, 2012). Munera et al (2017bMunera et al ( & 2017a analysed the astringency and the internal quality of persimmon using hyperspectral imaging, which has the advantage of obtaining both spectral and spatial information. However, one of the most common techniques currently used in food chemistry is near-infrared (NIR) spectroscopy, as it is non-destructive, inexpensive, rapid and reliable (Nicolaï et al, 2007;Vitale et al, 2013;López et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, this technique has been used recently to evaluate astringency, tannin content and internal quality of intact persimmons …”
Section: Introductionmentioning
confidence: 99%